THE EFFECT OF SHARIA BANKING STUDENTS' PERCEPTIONS ABOUT SHARIA BANKING ON INTEREST IN CHOOSING SHARIA BANK PRODUCTS - Isti Adzah Haniefah Luthfiah; Rian Hidayat Siregar; Wahyu Hidayat; Siti Asyifah; Henny Saraswati (Moneta: Jurnal Manajemen & Keuangan Syariah, 2023)
This study aims to determine the effect of student perceptions of the Islamic banking sector on their interest in choosing products from Islamic banks. This research is quantitative in nature, namely to find out how much influence students' perceptions of the Islamic banking sector have on their interest in choosing Islamic financial products. 36 student interviews were conducted to collect research data. Validity test, reliability test, descriptive analysis, simple linear regression analysis, and T-score test (partial test) were all used in data analysis. With a significance level of 0.000-0.005, the findings show that students' perceptions of Islamic banking are positively correlated with their decision to use Islamic financial products. The regression formula used is Y = 1.177+ 0.714 X.